Evaluation of the Functional Status of Signal Systems of Astrocytes by the Developed Reagent Kit Basedon Genetic Constructions (Experimental Study) - Silina, Ekaterina Vladimirovna (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: The objective of the study was to create a new type of therapy for neurodegenerative diseases; we have conducted a study with the goal to develop techniques based on functional and/or genetic constructions for the control of exocytosis based on a modification of the vesicles of brain astrocytes. Materials and Methods: For this purpose, we made specific transfection of astroglial cells by an experimental sample of the reagent kit developed by the authors. It represents genetic construction lentiviral vector (LVV) - glial fibrillary acidic protein (GFAP) -Case12 on the basis of a LVV. Results and Discussions: We can see results of introduction of the genetic construction into astroglial cells of adult Wistar rats, consisting in the activation of intracellular cascades. A comparison of the astrocytic response to ionomycin on organotypic cuts transfected with LVV-GFAP-Case12 was performed as well as on the organotypic cuts of the model of hepatic encephalopathy. This allowed us to objectively assess the astrocytic signaling systems, their overall functional status on modification of astrocytes of the cortex and brainstem in healthy rats in vivo, as well as in animal models of hepatic encephalopathy. Conclusion: In case of the model of hepatic encephalopathy, an amplitude of the astrocytic response to ionomycin was significantly reduced, which indicates pathological processes in the brain cells in this pathology, and also characterizes the developed genetic construction as an effective tool for assessing pathophysiological mechanisms occurring in the brain.